What drives the private innovation in rural areas? In-depth case study of Slovak rural region - Hrivnák Michal; Roháčiková Oľga; Schwarcz Pavol (Administrative Sciences, 2020)
Innovation and small fast-growing knowledge-intensive enterprises are often described as a potential engine for development of rural economies of the post-socialistic countries, struggling with problem of depopulation, decline of agriculture, monostructural economic base, overexploitation of natural resources and many others. However, we still know too little about, how private innovation emerge in underdeveloped space or how knowledge-intensive economic activities can successfully operate in small municipalities, providing almost non business services, basic infrastructure or potential for local networking. Thus, in this regional case study, we wanted to shed a light on a phenomenon of private innovation emergence in small rural settlements, provide baseline knowledge about motivation and determining factors of development of the innovative business in the rural, local economies. Special attention was devoted to examining the relationship between family entrepreneurship, residence of entrepreneur, interest to contribute to solution of local challenges and localization of knowledge-intensive business in rural municipality.
Keywords: 350; innovation; local economic development; private sector; rural economy